Employability prediction based on personality test using Naive Bayes Algorithm / Mohd Alief Mukhlis Mohd Adnin - Mohd Adnin, Mohd Alief Mukhlis (2020)
In the past, employability studies have mainly focused on human capital attributes and demographic factors (Wille, De Fruyt, & Feys, 2013). However, employability is not only determined by the knowledge, skills, and abilities an individual possesses, but also requires other latent, higher-order personality trait that facilitates an individual's ability to adapt to changing work environment and career patterns (Fugate et al., 2004). Student who pursuing their studies in specific field must know their capabilities to that area. Without consideration of self-capabilities, this will affect them in future working environment. Moreover, there are some case of employees that quit their jobs due to depression and pressure at work. This happens due to taking less care of personality traits of employees in working environments. So, it is better to taking care such personality as an important aspect in employability in the future. The purpose of this project was to identify the personality type of person that can be used for employability prediction, to design a prototype model of prediction using Naive Bayes algorithm and to test the functionality the proposed prototype. The finding of this project is this project are able to predict the user employability by taking care of their personality traits through personality test. For future work, recommendation of this project is to do more comprehensive integrating employability research across different domains and levels such as proactive personality, willing and ability and to measure the predictive power of these traits including the Big Five in relation to employability.